Long-term follow-up after successful treatment of vaccine-induced prothrombotic immune thrombocytopenia. Issue 207 (November 2021) - Thaler, Johannes; Jilma, Petra; Samadi, Nazanin; Roitner, Florian; Mikušková, Eva; Kudrnovsky-Moser, Stephan; Rettl, Joachim; Preiss, Raphael; Quehenberger, Peter; Pabinger, Ingrid; Knoebl, Paul; Ay, Cihan
Abstract: Background: Cases of ChAdOx1 nCoV-19 (AstraZeneca) vaccinated patients with thrombocytopenia, elevated D-dimer, and elevated platelet factor 4 (PF4) antibody levels with- and without thrombosis have been reported. No recommendations regarding the duration of anticoagulation have been made, because data on the long-term course beyond the first weeks is lacking. Objective: To report on the treatment, medical course, and longitudinal follow-up of laboratory parameters in patients with vaccine-induced prothrombotic immune thrombocytopenia (VIPIT). Patients: We followed VIPIT patients with- ( n  = 3) and without (n = 3) venous thromboembolism fulfilling the aforementioned laboratory criteria. Results: Elevated D-dimer (median: 35.10 μg/ml, range: 17.80–52.70), thrombocytopenia (42 G/l, 20–101), and strong positivity in the platelet factor 4 (PF4)/heparin-enzyme-immunoassay (2.42 optical density [OD], 2.06–3.13; reference range < 0.50) were present in all patients after vaccination (10 days, 7–17). Routine laboratory parameters rapidly improved upon initiation of treatment (comprising therapeutic non-heparin anticoagulation in all patients and high dose immunoglobulins ± corticosteroids in 5 patients). PF4 antibody levels slowly decreased over several weeks. Patients were discharged in good physical health (8 days, 5–13). VIPIT did not recur during follow-up (12 weeks, 8–17). Five of 6 patients fully recovered (in 2 patients thrombosis had resolved, in 1 patient exertional dyspnea persisted). Conclusions: Remissions without sequelae can be achieved upon rapid initiation of treatment in patients with VIPIT. Platelet factor 4 antibody levels slowly decreased over several weeks but VIPIT did not recur in any of our patients. Continuation of anticoagulation in VIPIT patients at least until PF4 antibody negativity is reached seems reasonable. Highlights: Vaccine-induced prothombotic immune thrombocytopenia (VIPIT) may manifest with- or without thrombosis Upon rapid initiation of treatment remissions without sequelae were achieved Platelet factor 4 antibody levels slowly decreased over several weeks At least until PF4 antibody negativity is reached, anticoagulation seems reasonable Our case series indicates that swift initiation of specific treatment (i.e. high dose IVIG and non-heparin anticoagulation) should also be advised for patients without thrombosis, because particularly in these patients chances of remissions without sequelae are high. In this study, we also provide long term follow-up data for the first time. We found that PF4 antibody levels only slowly decreased over several weeks. Interestingly, vaccine induced prothrombotic immune thrombocytopenia did not recur in any of our patients despite high PF4 antibody levels over a relatively long period of time.